A novel method for Al/SiC composite fabrication: Lost foam casting - Guler, Kerem A.; Kisasoz, Alptekin; Karaaslan, Ahmet (CARL HANSER VERLAG, 2011)
In this paper, an innovative manufacturing approach to cast metal-matrix composite is proposed. Aluminum matrix composite production by lost foam casting has been investigated. In order to produce metal-matrix composite by lost foam casting, expanded polystyrene boards were designed as sandwich shaped and three layered. SiC particulates with 60 pm average grain size were settled between the board layers, while A6063 and A413 aluminum alloys were used as matrix materials. The effect of the matrix materials on the mechanical properties of the composite specimens was investigated and fabricated specimens were characterized using image analysis, hardness tests, scanning electron microscope and X-ray diffraction analysis. The results show that in the lost foam casting method, the hardness of the A6063 and the A413 materials specimens increases with SiC reinforcement up to 70% and 80%, respectively.
Keywords: MMC's; SEM; XRD; Casting; ALUMINUM-MATRIX COMPOSITES; PRESSURE; Metallurgy & Metallurgical Engineering